SAT-303 3D Mapping of the Human Growth Hormone Locus Identifies Putative Regulatory Hubs for Genes Involved in Cellular Signalling and Cancer-Related Pathways - Jain, Lekha (J Endocr Soc, 2020)
Growth hormone (GH) is a peptide hormone predominantly produced in the pituitary that is crucial for normal growth and metabolism. Downstream effects of GH are mediated through binding to the GH receptor (GHR) and consequent activation of key signalling cascades including JAK-STAT, MAPK, PI3K-Akt and mTOR. The GH locus is comprised of five evolutionarily related genes under the control of an upstream locus control region which coordinates tissue-specific expression of these genes in the pituitary and placenta (1). Compromised GH signalling and genetic variation in these genes has been implicated in various disorders including cancer. We hypothesised that polymorphisms which occur within the GH locus have the potential to impact on disease phenotypes by altering or disrupting gene regulation. We used the CoDeS3D (Contextualize Developmental SNPs using 3D Information) algorithm to analyse 529 common single nucleotide polymorphisms (SNPs) across the locus. This algorithm identifies colocalised Hi-C and eQTL associations to determine which SNPs are associated with a change in gene expression at loci that physically interact within the nucleus. We identified 181 common SNPs that interacted with 292 eGenes in 48 different tissues. 145 eGenes were regulated in trans. We performed pathway enrichment of identified eGenes and found these to be enriched in GH/GHR-related downstream cellular signalling pathways including MAPK, PI3K-Akt-mTOR, and ErbB signalling. Enrichment was also observed in the Wnt and Hippo signalling pathways. There was also a significant representation of these eGenes in pathways associated with hepatocellular, colorectal, breast and non-small cell lung carcinoma. 33 eQTL SNPs identified in our study were found to be of regulatory importance in a genome-wide Survey of Regulatory Elements (SuRE) reporter screen (2). In addition, 7 eQTL SNPs were located in known enhancer regions. Our data suggests that regions within the GH locus form regulatory hubs for multiple genes in cis and trans (intra and inter-chromosomal), many of which are involved in mediating GH function in normal and pathogenic states. Reference: (1) Tsai et al. Nucleic Acids Res 2016, 44, 10, 4651 (2) van Arensbergen et al. Nat Genet 2019, 51, 7, 1160.